Deciphering the Epidemiological Characteristics and Molecular Features of blaKPC–2- or blaNDM–1-Positive Klebsiella pneumoniae Isolates in a Newly Established Hospital - Ruifei Chen; Ziyi Liu; Ziyi Liu; Poshi Xu; Xinkun Qi; Shangshang Qin; Zhiqiang Wang; Ruichao Li; Ruichao Li (Frontiers in Microbiology, 2021)
The emergence of hypervirulent carbapenem-resistant Klebsiella pneumoniae (hv-CRKP) was regarded as an emerging threat in clinical settings. Here, we investigated the prevalence of CRKP strains among inpatients in a new hospital over 1 year since its inception with various techniques, and carried out a WGS-based phylogenetic study to dissect the genomic background of these isolates. The genomes of three representative blaNDM–1-positive strains and the plasmids of four blaKPC–2-positive strains were selected for Nanopore long-read sequencing to resolve the complicated MDR structures. Thirty-five CRKP strains were identified from 193 K. pneumoniae isolates, among which 30 strains (85.7%) harbored blaKPC–2, whereas the remaining five strains (14.3%) were positive for blaNDM–1. The antimicrobial resistance profiles of blaNDM–1-positive isolates were narrower than that of blaKPC–2-positive isolates. Five isolates including two blaNDM–1-positive isolates and three blaKPC–2-positive strains could successfully transfer the carbapenem resistance phenotype by conjugation. All CRKP strains were categorized into six known multilocus sequence types, with ST11 being the most prevalent type. Phylogenetic analysis demonstrated that the clonal spread of ST11 blaKPC–2-positive isolates and local polyclonal spread of blaNDM–1-positive isolates have existed in the hospital. The blaNDM–1 gene was located on IncX3, IncFIB/IncHI1B, and IncHI5-like plasmids, of which IncFIB/IncHI1B plasmid has a novel structure. By contrast, all ST11 isolates shared the similar blaKPC–2-bearing plasmid backbone, and 11 of them possessed pLVPK-like plasmids. In addition, in silico virulome analysis, Galleria mellonella larvae infection assay, and siderophore secretion revealed the hypervirulence potential of most blaKPC–2-positive strains. Given that these isolates also had remarkable environmental adaptability, targeted measures should be implemented to prevent the grave consequences caused by hv-CRKP strains in nosocomial settings.